Penerapan Media Digital dalam Evaluasi Pembelajaran Sekolah Dasar: Studi Observasi Lapangan - Muhammadi M; Ranti Meizatri; Shafira Nuraini Alya; Wahyu Tia Anisa; Nazuwa Kanza Azzahra; Yahsa Aprilami Sepa (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Digital-based learning evaluation has become an important component of the learning process in elementary schools in line with the rapid development of information and communication technology. This study aims to describe the implementation of digital-based learning evaluation, the types of evaluation media used, the suitability of the media to learning materials, as well as the responses and challenges experienced by students and teachers. This research employed a descriptive qualitative approach using an observation method conducted in eight elementary schools in West Sumatra Province. Data were collected through direct classroom observations, brief interviews with teachers, and documentation of digital learning evaluation activities. The results indicate that digital-based learning evaluation has been implemented in a structured manner and integrated into the learning process, particularly at the final stage of instruction. The evaluation media used include Wordwall, Educaplay, Google Forms, and Kahoot, with interactive game-based media being more dominantly applied due to their suitability to the characteristics of elementary school students. Students’ responses to digital evaluation were generally positive, as reflected in increased enthusiasm, focus, and engagement during evaluation activities. However, this study also identified several challenges, such as limited facilities, unstable internet connectivity, and varying levels of digital literacy among teachers and students. Therefore, adequate infrastructural support and continuous improvement of teachers’ digital competencies are required to ensure that digital-based learning evaluation can be implemented optimally and sustainably.